THE ASYMMETRIC EFFECT OF REAL INTEREST RATE ON INDUSTRIAL OUTPUT IN NIGERIA - Kabir Mohammed, Risqot; BERNARD, Ojonugwa Anthony; Yakubu, Alfa; Salihu, Ayodeji (Kashere Journal of Management Sciences, 2024)
This study investigates the asymmetric effect of real interest rate on industrial Output in Nigeria using the linear and nonlinear autoregressive distributed lag techniques. Quarterly time series data sourced from CBN Statistical Bulletin (2022) spanning 1986: Q1 to 2022: Q4 for industrial production index (IPI) which is the dependent variable and real interest rate (RNTR), inflation rate (INFR) and exchange rate (EXHR) which are considered explanatory variables. Major findings from this study show the existence of a long-run co-integrating relationship among the variables. However, further findings revealed the absence of an asymmetric effect of real interest rate on industrial production in Nigeria. Real interest rate has a significant negative effect on industrial production in the long run and short run holding all other variables constant, hence, concluding that there is no asymmetry in the effect of interest rate on industrial production in Nigeria. Therefore, the study recommends Central Bank of Nigeria embark on monetary policies that will reduce real interest rates, allow for credit accessibility for owners of industries and hence productivity and output.